Intelligent IoT for the digital world : incorporating 5G communications and fog/edge computing technologies - Yang, Yang, 1974- (John Wiley & Sons, Inc., 2021)
"This book focuses on a novel type of Internet of Things (IoT) architecture, i.e., Web of Things (WoT) with open character, which naturally breaks the barriers among various IoT vertical applications. Key technologies from physical to platform level are presented and compared, especially the Narrow Band Internet of Things (NB-IoT) technology. Applications that are typical to IoT are discussed with different data transmission requirements. In the book's first part, the requirements of WoT applications on 5G is described. Next, detailed information on WoT technologies are presented. Later, three typical WoT applications are introduced, including the monitoring application of south-to-north water diversion projects, smart driving applications, and network optimization applications. Lastly, the authors explore testing and authentication of IoT key technologies, together with the required equipment, platform, and outdoor environment development"--